Akinetic mutism in a patient with mild traumatic brain injury: A diffusion tensor tractography study - Jang, Sung Ho; Kwon, Hyeok Gyu (Brain injury, 2017)
Akinetic mutism (AM) is characterized by a complete absence of spontaneous behaviour and speech. We report on a patient with AM associated with injury of the prefronto-caudate tract and prefronto-thalamic tract following mild traumatic brain injury (TBI), diffusion tensor tractography (DTT). A 20-year-old man suffered from TBI resulting from a pedestrian car accident. Following the TBI, he developed abulia (decreased activity and speech) that worsened over approximately a year. His typical features of AM that remained stable from one year until two years after the TBI are: he showed no spontaneous movement or speech and remained recumbent with no spontaneous activity. On one-month DTT, the neural connectivity of the caudate nucleus to the medial prefrontal cortex was low in both hemispheres, and this neural connectivity was lower on two-year DTT. The orbitofrontal-thalamic tract was thin in the left hemisphere on one-month DTT, whereas this tract became thinner in both hemispheres on two-year DTT. Using serial DTTs, injuries of the prefronto-caudate tract and orbitofrontal-thalamic tract and degeneration of these injured neural tracts concurrent with aggravation of abulia to AM were demonstrated in a patient with mild TBI. ABBREVIATIONS AM akinetic mutism; BA Brodmann areas; CN caudate nucleus; CST corticospinal tract; CRT corticoreticulospinal tract; DTT diffusion tensor tractography; FAC Functional Ambulation Category; PFC prefrontal cortex; MMSE Mini-Mental State Examination; ROI region of interest; TBI traumatic brain injury.